Micro-finance Competition with Motivated MFIs - GUHA, Brishti (Institutional Knowledge at Singapore Management University, 2012)
In this paper we examine the effect of increased MFI competition, focusing on its implications for borrower targeting, both in the presence and the absence of double-dipping. In the absence of competition we find that the loans are more likely to go to relatively richer borrowers whenever inequality is not too large, and the technology is sufficiently convex. In the presence of competition, the results depend on whether double-dipping is feasible or not. In case double-dipping is not feasible, we find that the MFIs necessarily target the richer borrowers. Interestingly, it turns out that double-dipping may encourage the MFIs to give loans to the poor, rather than the rich. Further, our analysis raises doubts regarding the benefits of encouraging coordination among the MFIs.